Pendampingan Digitalisasi Sekolah Untuk Meningkatkan Technological Pedagogical Content Knowledge (TPACK) - Nursaadah, Euis Nursaadah; Gumono (CARADDE: Jurnal Pengabdian Kepada Masyarakat, 2023)
SMPN 02 Tebatkarai Bengkulu, is a pilot school chosen to implement an independent curriculum through the Mobilization School program as part of a community of practitioners to innovate with the competencies and values of the Pancasila profile. The government has provided an independent teaching platform that can be utilized by teachers in the learning process, leading to digitalization. This is inseparable from TPACK's skills in integrating digital aspects as a technological component with other aspects of PCK. Through the I-CARE training method. Activities are carried out by introducing the importance of the TPACK component. Its application is carried out by guiding teachers to design TPACK and Reflection-based learning by linking the suitability of learning objectives and evaluation by analyzing the resulting TPACK design. The results of the training show that partners are able to connect the 7 aspects of TPACK with a percentage of 76% being able to use technology, 56% having good content knowledge, 74% having good pedagogical competence, 56% of partners being able to connect pedagogy with content, 75% partners being able to connect technology with content, 64% are able to relate technology, pedagogy and content and 50% are able to relate TPACK aspects in their learning design